Correlation Between Serum Uric Acid and Body Fat Distribution in Patients With Polycystic Ovary Syndrome - Zhang, Yuqin; Cai, Meili; Dilimulati, Diliqingna; Lin, Ziwei; Sun, Hang; Cui, Ran; Fei, Hongxiang; Gao, Xinxin; Zeng, Qiongjing; Shao, Xiaowen; Zhang, Manna; Qu, Shen (Frontiers in Endocrinology, 2022)
Objective: This study aims to investigate the correlation between serum uric acid levels and body fat distribution in patients with polycystic ovary syndrome (PCOS). Methods: A retrospective analysis of 201 patients with PCOS who visited the Department of Endocrinology and Metabolism at the Shanghai Tenth People’s Hospital between May 2017 and March 2021. Anthropometric characteristics, metabolic parameters and reproductive hormones were measured. Hyperuricemia was defined as serum uric acid (SUA) greater than 420 umol/L. Dual-energy X-ray absorptiometry (DEXA) was used to measure body fat distribution. Results: The prevalence of hyperuricemia in patients with PCOS was 28.86%. PCOS patients with hyperuricemia are more obese and have higher systolic blood pressure (SBP), worser insulin resistance (IR) and lipid metabolism than those without hyperuricemia. According to SUA quartiles, patients in the highest quartile had higher total testosterone (TT), body fat accumulation and lower sex hormone binding globulin (SHBG) than patients in the lowest quartile. By correlation analysis, SUA was correlated with total body % fat, arms fat mass, legs fat mass, trunk fat mass, android/gynoid (A/G) ratio, visceral adipose tissue (VAT) mass, VAT volume, VAT area, visceral adipose tissue / subcutaneous adipose tissue (VAT/SAT) ratio. After controlling possible confounders, logistic regression analysis found that only excessive VAT mass could significantly increase the risk of hyperuricemia in patients with PCOS. Conclusion: In patients with PCOS, high level of VAT mass, but not other fat compartments, will exacerbate the risk of hyperuricemia. Attention should be paid to the role of excessive VAT in the occurrence and development of PCOS with hyperuricemia.